Human and rodent pancreatic β-cells express IL-4 receptors and IL-4 protects against β-cell apoptosis by activation of the PI3K and JAK/STAT pathways. Issue 3 (15th December 2009) - Kaminski, Anna; Welters, Hannah J.; Kaminski, Edward R.; Morgan, Noel G.
Abstract : Secretion of pro-inflammatory cytokines is associated with loss of pancreatic β-cell viability and cell death. IL-4 (interleukin-4) has been reported to mediate a protective effect against the loss of pancreatic β-cells, and IL-4 receptors have been found in rat pancreatic β-cells at both the RNA and the protein level. The aim of the present study was to investigate IL-4 receptor expression in human islet cells and to examine the signalling pathways by which IL-4 exerts its effects using the rat β-cell lines, BRIN-BD11 and INS-1E. By means of immunohistochemistry, it was demonstrated that IL-4 receptors are present on human islet cells. Using a flow cytometric method for evaluating cell death, it was confirmed that incubating β-cells with IL-4 attenuated cell death induced by IL-1β and interferon-γ by approx. 65%. This effect was abrogated by the presence of the PI3K (phosphoinositide 3-kinase) inhibitor, wortmannin, suggesting that activation of the PI3K pathway is involved. In support of this, Western blotting revealed that incubation of cells with IL-4 resulted in increased phosphorylation of Akt (also called protein kinase B), a downstream target of PI3K. Increased tyrosine phosphorylation of STAT6 (signal transducer and activator of transcription 6) also occurred in response to IL-4 and a selective JAK3 (Janus kinase 3) inhibitor reduced the cytoprotective response. Both effects were prevented by overexpression of the tyrosine phosphatase, PTP-BL (protein tyrosine phosphatase-BL). We conclude that IL-4 receptors are functionally competent in pancreatic β-cells and that they signal via PI3K and JAK/STAT pathways. These findings may have implications for future therapeutic strategies for the management of diabetes.